Language Equation: Enchancing Stories Writing Skill - Sakulkaew Kaewmulkit (Bandar Lampung University (UBL), 2014)
This research paper was mainly focused on writing skill development amongst Thai second language learners. Many Thai English learners tend to concentrate on building examination skill; however, the four communicative skills (listening, speaking, reading and writing) are not focused. For many learners, writing is considered the hardest productive skill to acquire the Standard English writing. This research paper aims to introduce alternative pedagogical technique inspired by George Kelly’s theory exploring humans’ cognitive learning in simplified manners. This alternative technique proposed in this research is originally derived from the mathematical foundation to enhance writing skill; therefore, the name ‘Language Equation (LE)’ will be used in this paper to refer to the technique. The experiment was conducted to compare results between the subjects’ pre-writing and post-writing test after learning LE within 36 hours. As a result, the subjects became more confident in writing and producing comprehensible stories with correct grammar.